Opportunities for improved heavy truck occupant protection in rollover and overhead loading impacts. Issue 2 (4th March 2018) - Friedman, K.; Hutchinson, J.; Mihora, D.; Stephens, M.
ABSTRACT: Driver compartments on medium and heavy trucks are essentially modular units that are applied to a chassis. The same cab is often utilised independent of what the rest of the truck application may be. However, the strength of the cabs has been found to be comparable to that of pickup trucks while the gross vehicle weights involved for the applications can be more than 10 times greater than their passenger vehicle counterparts. In this study, the background to the problem is reviewed. An example baseline cab configuration is then examined under various rollover loading and top loading conditions utilising virtual testing techniques. Under the same conditions, alternative design approaches are considered and evaluated. The results indicate that opportunities are available to provide substantially better improved compartment strengths to maintain the survival space for medium and heavy truck drivers.